2013
DOI: 10.4103/0970-9371.107507
|View full text |Cite
|
Sign up to set email alerts
|

Leishman Giemsa cocktail as a new, potentially useful cytological technique comparable to Papanicolaou staining for oral cancer diagnosis

Abstract: Background:Papanicolaou staining is commonly used for staining exfoliative cytology smears with Romanowsky stains being used sparingly. Leishman Giemsa (LG) cocktail, being a relatively new staining technique, has not been used in exfoliative cytology. This easy, cost-effective and one-step technique warrants further study because of its potential application in screening of oral cancer.Aim:To study and evaluate the diagnostic efficiency and reliability of Leishman Giemsa (LG) cocktail in comparison with Papan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…The nucleus reveals less dark pyknotic staining, and the cytoplasm shows a better hue of colour differentiation with lighter colouration shades. These distinct characteristics are typical of a good Pap staining and have been reported [13,14] ; while, the background appears clear and more revealing compared to RAT (Figure 2). Furthermore, the staining uptake for SAP reveals prominent superficial and intermediate cells which appear distinct and well differentiated.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The nucleus reveals less dark pyknotic staining, and the cytoplasm shows a better hue of colour differentiation with lighter colouration shades. These distinct characteristics are typical of a good Pap staining and have been reported [13,14] ; while, the background appears clear and more revealing compared to RAT (Figure 2). Furthermore, the staining uptake for SAP reveals prominent superficial and intermediate cells which appear distinct and well differentiated.…”
Section: Discussionsupporting
confidence: 81%
“…In respect to the turn-around time, SAP (5±0.5) partially aligns with MEM (7±0.5) by Odigie and Obaseki [1] and the report by Choudhary et al [4] but is dissimilar to RAT as reported by Richard [5] . In an earlier report, SAP staining quality agrees with MEM, which was well preserved even after some months of storage and is essential for smear review and retrospective studies [1,8,13,14] . Again, we stored the left over stains used for the three modified Papanicolaou methods and observed that the stains are well preserved in both MEM and SAP apart from being very active in smear staining even after one year (April 2016 to April 2017).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The typical colour of nucleus is due to the molecular interaction between eosin and Azure B‐DNA complex. Leishman Giemsa (L‐G) cocktail, being a relatively new staining technique used previously for cytology smears , is largely unexplored and not documented in haematology for staining of peripheral blood/bone marrow smears. We created a newer modification of the conventional Leishman and Giemsa stains as a Leishman and Giemsa (L&G) stain, for staining the peripheral smear and bone marrow aspirate smears, and compared the efficacy and reliability of this stain with these conventional stains.…”
Section: Introductionmentioning
confidence: 99%